2014
DOI: 10.1037/a0034885
|View full text |Cite
|
Sign up to set email alerts
|

Constructive episodic simulation: Dissociable effects of a specificity induction on remembering, imagining, and describing in young and older adults.

Abstract: According to the constructive episodic simulation hypothesis (Schacter & Addis, 2007), both remembered past and imagined future events rely heavily on episodic memory. An alternative hypothesis is that observed similarities between remembering and imagining reflect the influence of broader factors such as descriptive ability, narrative style, or inhibitory control. We attempted to distinguish between these two hypotheses by examining the impact of an episodic specificity induction on memory, imagination, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
253
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(296 citation statements)
references
References 61 publications
39
253
4
Order By: Relevance
“…Consistent with previous work (Addis, Wong & Schacter, 2008;B. Levine et al, 2002;Gaesser, Sacchetti, Addis & Schacter, 2011;Madore, Gaesser & Schacter, 2014), the results of the present study showed that older adults recalled more semantic information than younger adults, thereby extending the previous findings to include recently acquired memories for everyday events.…”
Section: Semantic Amsupporting
confidence: 92%
“…Consistent with previous work (Addis, Wong & Schacter, 2008;B. Levine et al, 2002;Gaesser, Sacchetti, Addis & Schacter, 2011;Madore, Gaesser & Schacter, 2014), the results of the present study showed that older adults recalled more semantic information than younger adults, thereby extending the previous findings to include recently acquired memories for everyday events.…”
Section: Semantic Amsupporting
confidence: 92%
“…For example, when young and older adults construct future simulations, young adults produce more internal details than older adults, whereas the opposite pattern is observed for external details (39)(40)(41). More recent work has shown that an episodic specificity induction-brief training involving a cognitive interview about a recent experience that guides individuals to focus on recollecting specific details of that experience-selectively increases the number of internal details that young and older adults generate when they construct future simulations while having no effect on external details (42). Nonetheless, more research is needed to help discriminate episodic and semantic simulation in terms of their phenomenological characteristics, susceptibility to cognitive manipulations, and neural correlates.…”
Section: Varieties Of Future Thinkingmentioning
confidence: 99%
“…It has been argued that people base their predictions on episodic simulations of the future and that episodic simulations of the future are often imperfect and hence, result in errors in prediction (e.g., essentialized simulations of parenthood that focus on the rewarding aspects of childrearing; 1). As noted earlier, recent studies have shown that people are able to generate more detailed simulations of the future when they are trained to report those details in the context of a cognitive interview about a recent experience (42). Whether specificity inductions could be used to enhance predictive accuracy awaits future research.…”
Section: Varieties Of Future Thinkingmentioning
confidence: 99%
“…6). After receiving an episodic specificity induction (vs. a control induction), participants subsequently remembered past and imagined future experiences with increased episodic but not semantic detail, and the specificity induction had no effect on details generated during tasks that do not draw on episodic memory, such as describing a picture (7) or defining and comparing words (8). We have also shown that the specificity induction boosts performance on such tasks as means-end problem solving (9,10) and divergent creative thinking (11) that have also been linked previously to episodic memory.…”
mentioning
confidence: 99%